The Effect of Diabetes Mellitus Gymnastic on The Risk of Diabetic Ulcer - Wiwi Rumaolat; Miranda Waas; Jurais Simal (Humanistic Network for Science and Technology (HNST), 2017)
Increased socioeconomic status, public health services, changes in lifestyle, increasing life expectancy, Indonesia experienced a shift in the pattern of diseases from infectious diseases to non-communicable diseases, Diabetes Mellitus is a collection of symptoms that arise in a person caused by an increase in sugar levels (glucose) blood due to insulin deficiency both absolute and relative. Complications Diabetes mellitus are twofold, acute complications (short term) and chronic (long term) complications. Acute complications consist of diabetic ketoacidosis (KAD), non-ketotic hyperosmolar (HNK), and hypoglycemia. Gymnastics Diabetes mellitus is generally beneficial for the management of diabetes mellitus, namely: controlling blood sugar, especially in type 2 diabetes mellitus, inhibiting and improving risk factors for cardiovascular disease, losing weight, improving musculoskeleal symptoms. The purpose of this study was to analyze the effect of diabetes mellitus gymnastics on the risk of diabetic ulcer in patients with Type 2 diabetes mellitus in Telaga Piru Hamlet, West Seram Regency. The type of research used is experimental Quasy research using the Two-Group Post Test Control Design approach. The sample used is 26 respondents. Data collection is carried out with an observation sheet with direct interviews. The data that has been collected is then processed and analyzed using the Microsoft Excel program computer and the statistical program (SPSS) version 24 with Mann Whytney test and significance = 0.05. From the results of bivariate analysis, there is an effect of diabetes mellitus gymnastics on the risk of diabetic ulcers (p = 0.002) Keywords: Diabetes Mellitus Gymnastics, Diabetic Ulcers